Styrylpyrone derivative (SPD), a novel DENV-2 NS3, NS5 and prM inhibitor; inhibited RNA replication, protein transcription and production of DENV-2 progeny particles - Noor Zarina Abd Wahab; Nazlina Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2025)
In the last few decades, dengue has become much more commonplace worldwide, and it is quickly spreading to other countries. As of right now, supportive care is the only available treatment for dengue infection as there are no approved antivirals. Although a DENV vaccine has recently been used in some countries, its indication is limited due to risk of severe dengue in certain individu. The present study was aimed to investigate the effects of styrylpyrone derivative (SPD) extracted from Goniothalamus umbrosus against DENV-2 prM, NS3, and NS5 genes and proteins. Gene expression analysis by qRT-PCR was done to investigate the level of gene expression at different DENV-2’s replication phases. In situ ELISA assay was used to evaluate the effects of SPD treatment on the protein expression of NS3, NS5, and prM. In silico molecular docking was used to understand the interactions between peptide with target proteins. SPD inhibited the formation of infectious mature virus particles in the process of DENV-2 replication cycle by modifying the expression of prM gene during the infection. In situ ELISA assay of infected cells confirmed that SPD inhibited prM, NS3, and NS5 proteins. Thus, the SPD has the ability to alter DENV-2 replication cycle at the replication phase and during the formation of infectious mature virus particles stage and reduce progeny infectivity. Molecular docking in silico analysis confirmed that SPD can interact with all selected virus proteins through hydrogen bonds and other interactions. This study proved that SPD has the potential as anti DENV-2 by interruption expression of DENV-2 NS3, NS5 and prM genes and proteins at RNA replication, protein transcription, virus particles maturation and progeny infectivity phases of viral replication cycle.